2022
DOI: 10.1186/s13018-022-03444-3
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between the degeneration and asymmetry of the lumbar multifidus and erector spinae muscles in patients with lumbar disc herniation with and without root compression

Abstract: Background The determination of muscle pathologies in lumbar disc herniation (LDH) and other conditions with low back pain is important for understanding low back problems and determining appropriate treatment methods. In patients with lumbar disc herniation with radiculopathy, elucidating the effect of root compression on the severity of muscle degeneration may predict the importance of alleviating root compression. For this purpose, magnetic resonance imaging (MRI) was used to compare the deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 95 publications
(161 reference statements)
0
5
0
Order By: Relevance
“…Indeed, another study conducted by the same authors demonstrated that fat infiltration exhibited a significant correlation with root compression, and the severity of fat filtration further escalated when root compression was present. [15] In our study, in which the multifidus cross-sectional area was calculated in patients with nerve compression, we found that the amount of protrusion had no effect on the cross-sectional area of the lumbar multifidus muscle. However, this was thought to be due to the measurement of the total cross-sectional area without isolating the fat infiltrates in the muscle, while calculating the cross-sectional area of the lumbar multifidus muscle.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…Indeed, another study conducted by the same authors demonstrated that fat infiltration exhibited a significant correlation with root compression, and the severity of fat filtration further escalated when root compression was present. [15] In our study, in which the multifidus cross-sectional area was calculated in patients with nerve compression, we found that the amount of protrusion had no effect on the cross-sectional area of the lumbar multifidus muscle. However, this was thought to be due to the measurement of the total cross-sectional area without isolating the fat infiltrates in the muscle, while calculating the cross-sectional area of the lumbar multifidus muscle.…”
Section: Discussionmentioning
confidence: 68%
“…There are studies in the literature on pain, physical function, and the cross-sectional area of the multifidus muscle in individuals with lumbar disc herniation. [13,14] Although there is a study demonstrating a correlation between lumbar disc herniation and paraspinal muscle degeneration, indicating that severe fat infiltration is associated with nerve root compression, and the severity of fat infiltration increases in the presence of nerve root compression, [15] we have not come across any research investigating the impact of protrusion size in lumbar disc herniation on pain, lumbar mobility, physical function, and the cross-sectional area of the lumbar multifidus muscle. This study was designed with the aim of exploring the relationship between the symptoms and the radiologically detected disc herniation and how it may manifest in the clinical presentation.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity measured using BMI or LFSTT is not the only risk factor for the development of lumbar hernias; however, different lumbar hernia prevalence rates have been reported depending on the area of the world where the study was conducted. Therefore, patients should be staged according to the states or countries where they reside or have lived most of their lives, as well as by their different ethnicities, races, and other socioeconomic and cultural conditions that may be risk factors for the increased presence of hernial defects in discs [ 19 , 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A cross-section study showed a correlation demonstrated between LDH and paraspinal muscles [ 132 ]. Some retrospective studies provide evidence for this viewpoint.…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%
“…Yazici et al. conducted a cross-section study and reported a correlation between the FI of the paraspinal muscles and LDH but did not find any correlation with asymmetry [ 132 ]. It is important to note that these conclusions may be attributed to differences in the study populations, methods, sample sizes, and other factors.…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%